Nutritional and Antioxidant Profiling of Vitamin K Dietary Sources - Yasin, Muhammad; Butt, Masood Sadiq; Anjum, Faqir Muhammad; Shahid, Muhammad (Pakistan Journal of Nutrition, 2013)
The present investigation was an effort to explore the nutritional profile and antioxidant indices of vitamin K dietary sources i.e., spinach and soybean. For the purpose, spinach and soybean were nutritionally characterized with special reference to vitamin K content. The proximate composition of spinach exhibited that moisture, crude protein, crude fat, crude fiber, ash and Nitrogen Free Extract (NFE) as 90.71±4.14, 2.03±0.95, 0.32±0.007, 0.58±0.02, 1.24±0.06 and 5.01±0.11%, respectively. However, tested soybean indicated the values respective traits as 8.96±0.45, 32.28±1.99, 18.64±1.02, 2.93±0.16, 3.38±0.19 and 33.79±1.15%. Furthermore, spinach showed good mineral profile dominated by magnesium, potassium and calcium whilst soybean is abundant in potassium, zinc and magnesium. The HPLC quantification of vitamin K revealed that spinach contained 379.09 μg/100g phylloquinone as compared to soybean 29.79 μg/100g. Amongst antioxidant extracts, methanolic extracts of spinach and soybean showed higher total phenolic, DPPH scavenging and antioxidant activities. In conclusion, spinach showed higher antioxidant status and phylloquinone as compared to soybean however, soybean contained ample amount of protein and fat contents.